WINDSHIELD DEFROST SIMPLIFIED CFD MODEL - Schmid, Michal (Univerzita Pardubice. Dopravní fakulta Jana Pernera, 2019)
The windshield defrost system, in general, is a vehicle safety feature. Thus, its restricted by variety of directives. However, the OMEs’ benchmark targets could be even more demanding as the deicing process is in addition also part of passengers comfort. From vehicle design point of view the windshield defrost system is typically connected to HVAC unit (Heating, Ventilation and Air Conditioning). In the technical solution the windshield is heated via hot air convection. Nevertheless, other methods are becoming more and more popular, like directly heated glass by hot wire ohmic heating (heated glasses). The defrost CFD model should predict the ice layer thickness in time and space and in environmental conditions defined according to appropriate directives and technical solution. The accurate and fast modelling technique is essential part of a vehicle development, especially nowadays, where the optimization techniques area widely used and requires hundreds of simulations runs. Modelling requests are even increasing with modern pure electric vehicles (EVs), were the thermal and energy management is more demanding compared to the classical internal combustion engine (ICE) vehicles. The aim of the work is to verify possibility to model the ice layer thickness with simplified approach, which could be beneficial from computational time burden.
Zjednodušený CFD model rozmrazování čelných skel
Keywords: Windshield defrost, CFD, ice layer thickness, VOF, Thin Film; rozmrazování čelních skel, CFD, tloušťka vrstvy ledu, VOF, tenký film